Leveraging Social Media Marketing for Enhanced Brand Visibility and Engagement: A Strategic Approach - N.Sangeetha; Priyadharshini, B.Indira (International Journal of Economics, Business Management and Accounting (IJEBMA), 2025)
Businesses now use social media marketing to improve their standing, encourage user involvement, and develop lasting links with consumers. This paper investigates how social media helps to promote brands and keep customers loyal to them. Everything in the paper focuses on major brand strategies companies are adopting, such as tailored content, working with influencers, using shared content, and engaging with online communities to appear more prominently. The study takes a look at Apple’s #ShotOniPhone, Coca-Cola’s “Share a Coke,” and Nike’s “Just Do It” influencer campaign to prove how they create strong outcomes for the organizations. Besides, the manuscript outlines the difficulties brands experience, including receiving too much information, changes in how algorithms work, and maintaining an honest image in front of the public. Since there are new trends like customized AI for marketing, live broadcasting, and online shopping through social media, this paper covers the future outlook of social media marketing and how it affects brand recognition. In brief, using online platforms for marketing calls for continuous adjustment to trends, fitting customers’ needs, and smart use of data to ensure steady growth of the brand